2022
DOI: 10.1016/j.biopsych.2022.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Development of Apathy, Anxiety, and Depression in Cognitively Unimpaired Older Adults: Effects of Alzheimer’s Disease Pathology and Cognitive Decline

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 57 publications
1
20
1
1
Order By: Relevance
“…For NHWs, total GDS and Dysphoria scores were related to Aβ40, a marker of amyloid burden. Apathy which was found to be related to Aβ pathology in the early stage of Alzheimer's in a Swedish study 35 was not be related either marker of amyloid in our cohort. When the level of depression as measured by the number of GDS items endorsed is analyzed for the total sample, those defined as depressed had higher levels of Aβ40, Aβ42 and NfL.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…For NHWs, total GDS and Dysphoria scores were related to Aβ40, a marker of amyloid burden. Apathy which was found to be related to Aβ pathology in the early stage of Alzheimer's in a Swedish study 35 was not be related either marker of amyloid in our cohort. When the level of depression as measured by the number of GDS items endorsed is analyzed for the total sample, those defined as depressed had higher levels of Aβ40, Aβ42 and NfL.…”
Section: Discussioncontrasting
confidence: 64%
“…A follow up study looking at additional CSF biomarkers found the depressed individuals had higher levels of Aβ42 and NFL. 14 Johansson et al 15 in a study of cognitively unimpaired older Swedes; found that CSF amyloid-β pathology predicted levels of apathy longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…There has been evidence showing that Neuropsychiatric Symptoms (NPSs), such as anxiety, apathy and irritability, are often associated with cortical damage of temporal lobe, middle frontal gyrus and limbic system in AD patients [19]. Aβ sedimentation is an important driving factor for the development of apathy and anxiety in the aged [20]. The frequency and severity of NPS may increase along with the deterioration of cognitive ability [21].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to amyloid‐PET imaging, most cross‐sectional studies reported associations between higher neuropsychiatric symptoms burden and higher amyloid load, 9–11,50,51 albeit some studies did not confirm this association 52,53 . Longitudinal studies also provided evidence of associations between neuropsychiatric symptoms, amyloid deposition, and cognitive decline, 54–56 and between abnormal amyloid deposition and higher neuropsychiatric symptoms over time 57–59 . With regard to tau‐PET imaging, one cross‐sectional study revealed significant associations between higher depressive symptoms with greater inferior temporal and entorhinal cortex tau in cognitively unimpaired older adults, 12 whereas another study showed that neuropsychiatric symptoms were associated with tau‐PET in the parietal association area, superior frontal, temporal, and medial occipital lobes 13 …”
Section: Discussionmentioning
confidence: 99%